Women's experiences with person-centered family planning care: Differences by sociodemographic characteristics - Kate Welti; Jennifer Manlove; Jane Finocharo; Bianca Faccio; Lisa Kim (Elsevier, 2022)
Objective: Person-centered contraceptive care is associated with positive reproductive health outcomes. Our objective was to analyze patients' ratings on the newly developed Person-Centered Contraceptive Counseling scale (PCCC) to provide distributions for a nationally representative population and to assess differences by sociodemographic characteristics. Study design: Using data from 2017 to 2019 National Survey of Family Growth (NSFG), we analyzed ratings across the four PCCC items among 2242 women who received contraceptive counseling in the past year. Items measured patients' reports of how providers respected them, let them describe their contraceptive preferences, took their preferences seriously, and adequately informed them about their options. We studied each PCCC item individually as well as the combined scale, distinguishing between ratings of "excellent" versus lower ratings. Bivariate and multivariate logistic regression models assessed how patients' characteristics (age, race/ethnicity and English proficiency, sexual orientation, income, and parity) and provider type were associated with the likelihood of experiencing person-centered care. Results: The majority of women (59%-69%) reported that their family planning provider was "excellent" across the four PCCC items and just over half (51%) reported "excellent" on all items. In multivariate analyses, having a lower income, Black race, non-heterosexual identity, and Hispanic ethnicity combined with low English proficiency were associated with lower PCCC ratings. Conclusions: In a nationally representative sample, the PCCC captured variation in women's experiences with person-centered family planning care by sociodemographic characteristics. Findings highlight the need for contraceptive counseling that centers on clients' preferences and experiences, particularly for patients who belong to groups experiencing health inequities. Implications: Person-centered care is a key component of high-quality family planning services. This analysis highlights sociodemographic disparities in person-centered care by analyzing PCCC ratings. Findings show the value of this new health care performance measure and affirm the need for family planning care that centers individuals' preferences and lived experiences.